Analysis of Work-Related Health and Safety Accidents in the Emirate of Sharjah - AlZarooni, Mohamed (2021)
A Master of Science thesis in Engineering Systems Management by Mohamed AlZarooni entitled, “Analysis of Work-Related Health and Safety Accidents in the Emirate of Sharjah”, submitted in April 2021. Thesis advisor is Dr. Mahmoud Awad. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).